A Scandinavian perspective on high-performance coaching: an ethically based balancing act between four interrelated knowledge dimensions - Gerrevall, P.; Hageskog, C. A.; Kjær, J. B.; Bjärsholm, D.; Linnér, S. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
This study aimed to formulate the characteristic features of Scandinavian successful high-performance coaching. We took our point of departure in the works of Côté and Gilbert (Citation2009, Citation2013) concerning the knowledge possessed by high-performance coaches. We interviewed 18 successful Scandinavian coaches who were deeply committed to their respective coaching assignments and had achieved great success through the performances of their practitioners at major championships. We then conducted a thematic analysis of the interview data, identifying, analysing and reporting patterns (themes). Our results show that Scandinavian high-performance coaching is a value-based and sensitive balancing act between four knowledge dimensions: analytical and systematic, authority and stability, relational and communicative, and innovative and creative development. The four dimensions, together with an ethical core, form the link between Côté and Gilbert (Citation2009) categorisation of high-performance coaches` knowledge base and how this knowledge is put into practice.